Comparison study on effects of overexpressing citrate synthase driven by light-inducible promoter and constitutive promoter on Al tolerance of transgenic tobacco plants - WANG Qi-feng; HU Qing-quan; ZHAO Yue; YI Qiong; LI Kun-zhi; YU Yong-xiong; CHEN Li-mei (浙江大学学报. 农业与生命科学版, 2011)
Overexpression of citrate synthase (cs) cDNA of tobacco was driven by the light-inducible promoter of rubisco small subunit (PrbcS) and the constitutive promoter CaMV 35S (35S) in transgenic tobacco plants, respectively. The changes in citrate contents and exudations as well as Al tolerances in transgenic PrbcS and 35S tobacco plants were compared. The results showed that CS enzyme activities were increased 2.3-2.4 folds and 1.6-2 folds in transgenic PrbcS and 35S tobacco plants as compared with wild tobacco (WT) plants, respectively. When exposed to 30 μmol·L-1 Al, relative root elongation rates of transgenic PrbcS and 35S tobacco plants were also increased 2.8-2.9 folds and 2-2.3 folds as compared with WT, respectively. Citrate contents in the transgenic tobacco leaves were significantly increased compared with the WT plants, which were especially pronounced in transgenic PrbcS tobacco plants. Citrate contents in the transgenic PrbcS tobacco roots and citrate exudation from their roots were elevated more effectively compared with transgenic 35S plants under acidic conditions with 300 μmol·L-1 Al3+ stress. When grown in a perlite medium supplied with 500 μmol·L-1 Al3+ nutritional solution twice a week, all transgenic tobacco lines showed better growth performance than the WT plants. The results above suggest that CS enzyme activity and citrate synthesis are increased more effectively in transgenic tobacco when cs overexpression is driven by PrbcS promoter. Consequently, citrate exudations and Al tolerance in transgenic PrbcS tobacco plants are also enhanced and improved more evidently compared with transgenic 35S ones.